The effect of forgiveness writing therapy on post-traumatic growth in survivors of sexual abuse. Issue 1 (2nd January 2019) - Ha, Neul; Bae, Sung-Man; Hyun, Myoung-Ho
ABSTRACT: The goal of the present study was to examine the therapeutic effects of forgiveness writing therapy in victims of sexual abuse, with an emphasis on their shame, depressive symptoms, and post-traumatic growth. South Korean participants who had experienced sexual abuse were randomly assigned to two groups ( M = 22.3 years, SD = 1.60; n = 16 per group): the forgiveness writing therapy (FT) group and the control group. The FT group participated in four writing sessions in which they wrote about self-forgiveness, situational forgiveness for 30 min; the control group did not participate in any particular treatment program. The results indicated significant group differences; compared to the control group, the FT group demonstrated a significant reduction in shame and depression, and an increase in post-traumatic growth. Implication and limitations of the present research, as well as suggestions for future research, are discussed.